SISTEM PENDUKUNG KEPUTUSAN ALTERNATIF PEMELIHARAAN GEDUNG SEKOLAH (Studi kasus: SLTP Negeri I Pakem) - Priyosulistyo, Hrc.; Sudarmoko, Sudarmoko (Civil Engineering Forum Teknik Sipil, 2008)
The performance of the building declines in line with the age of the building. To maintain the performance of the building, the building maintenance should be carried out. For this reason, an adequate program that able to analyze cost as well as condition of the building has been developed in this research. The assessment was carried out in a secondary school building in Pakem Sub Regency of Yogyakarta. The research used Analyzes of Hierarchy Process (AHP). Besides, the maintenance cost was also considered in the analysis. The secondary school has several buildings. Each building consists of structural, architectural and utilities components. This research mainly studied the performance of the architectural components rather than other components. The architectural components consists of classrooms, office rooms and supporting rooms. In every room, architectural element such as ceiling, wall, window, door and floor are subdivided into their accompanying elements. The elements were then weighted in accordance with their functions. The severities of their conditions were assessed in terms of percentage of the deterioration. The residual condition was determined by reducing the index condition (100 is best condition). The accumulative index condition was then represented the condition of every room. The determination of the priority was carried out on the basis of the ratio between increment of the condition (from the existing condition to the best condition) and the cost implied on the maintenance. The priority would go to the highest ratio. An analysis result indicate that among 37 rooms perceived, the class rooms obtained first priority followed by office room and then supporting room. The three first sequence priority among sixteen class rooms are classroom VIIA, the natural science laboratory and classroom IIIA. Among four rooms in office room groups, three first priority are Teacher room, Administration room, Headmaster room, and among seventeen room of supporting room groups, the three first priorities are parking area, canteen room, medical room.